(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Family allowance for social protection of children is defined in the Law on Protection of Children, as follows: children allowance, special allowance, single financial assistance for a new-born child and parental allowance for a child. The thesis deals with the most common social financial assistance for the family with children and their right to child allowance. Most often, the child allowance is granted to all families whose total family income is below a certain financial threshold and is designed to help cover the costs of supporting a child to a certain age. Sometimes this right is conditioned by the employment of parents, schooling of children, vaccines and health examinations. The European Union Law prescribes that child’s allowances/benefits of the child allowance are taken over the country of residence where the EU citizen lives or works, regardless of the nationality. Thus, by applying the comparative method, the thesis makes an overview of the realization of the right to child allowance in some of the EU countries. Using the legal and sociological method, an analysis of the right to child allowance in the Republic of North Macedonia is also elaborated. Further in the thesis, a combination of quantitative and qualitative research methods is used, analysing secondary data. The main instrument used in the thesis analysis is the critical review of the applicable legislation concerning the right to child allowance and the system of social protection of children.